Identifying STEVE's Magnetospheric Driver Using Conjugate Observations in the Magnetosphere and on the Ground. Issue 22 (21st November 2019) - Chu, Xiangning; Malaspina, David; Gallardo‐Lacourt, Bea; Liang, Jun; Andersson, Laila; Ma, Qianli; Artemyev, Anton; Liu, Jiang; Ergun, Robert E.; Thaller, Scott; Akbari, Hassanali; Zhao, Hong; et al.
Abstract: The magnetospheric driver of strong thermal emission velocity enhancement (STEVE) is investigated using conjugate observations when Van Allen Probes' footprint directly crossed both STEVE and stable red aurora (SAR) arc. In the ionosphere, STEVE is associated with subauroral ion drift features, including electron temperature peak, density gradient, and westward ion flow. The SAR arc at lower latitudes corresponds to regions inside the plasmapause with isotropic plasma heating, which causes redline‐only SAR emission via heat conduction. STEVE corresponds to the sharp plasmapause boundary containing quasi‐static subauroral ion drift electric field and parallel‐accelerated electrons by kinetic Alfvén waves. These parallel electrons could precipitate and be accelerated via auroral acceleration processes powered by Alfvén waves propagating along the magnetic field with the plasmapause as a waveguide. The electron precipitation, superimposed on the heat conduction, could explain multiwavelength continuous STEVE emission. The green picket‐fence emissions are likely optical manifestations of electron precipitation associated with wave structures traveling along the plasmapause. Key Points: The magnetospheric driver of STEVE is investigated using clear conjunction observations when Van Allen Probes directly crossed STEVE STEVE corresponds to a sharp plasmapause with SAID electric field, parallel electron acceleration collocated with kinetic Alfvén waves Multiwavelength continuous STEVE emissions are likely powered by parallel electron precipitation superimposed on heat conduction